Media Alternatif Tepung Maizena Untuk Pertumbuhan Jamur Trichophyton rubrum - Anas Fadli Wijaya; Rian Anggia Destiawan (Jurnal Kesehatan, 2021)
Infectious diseases due to microbes in Indonesia are mostly caused by fungal infections. One of these microbes is Trichophyton rubrum. There are several ways to diagnose dermatophytosis, but in general it is done clinically, then confirmed by microscopic examination and culture. The commercial media that is often used for culturing mushrooms is Potato Dextrose Agar (PDA). PDA media is a semi-synthetic medium with a high carbohydrate content. One ingredient that contains high carbohydrates is cornstarch. The purpose of this study was to determine the potential of cornstarch as an alternative medium for the growth of the fungus T. rubrum. This research is a laboratory experimental study with the post test control group design only method using 16 replications and 2 treatments, namely PDA media as a control and cornstarch media as an alternative medium. The results showed that the average number of T. rubrum growth on PDA media was 163.94 colonies while on alternative media cornstarch was 35.51 colonies. The value of p = 0.000 with a 2-way significance level (α = 0.05) then p <α. So there is a significant difference between the number of T. rubrum fungus colonies on PDA media and cornstarch alternative media. Cornstarch alternative media can be used as an alternative medium for the growth of T. rubrum but not as optimal as PDA media.